(untitled) (Swiss Medical Weekly, 2018)
AIMS OF THE STUDY Video documentation is nowadays well established in many fields of medicine, but mostly in unreal situations such as simulation training. We here present the application of video for teaching and learning purposes during the birth process. The aim of video documentation during labour is to provide an observational tool for obstetric care by midwives and obstetricians, with the opportunity for evaluation and education afterwards, especially in absence of the woman in labour and her family. METHODS Between February 2015 and June 2017, we conducted a prospective observational study on women aged over 18 years with singleton pregnancies with vertex presentation at term, who gave birth vaginally in the labour ward at the Division of Obstetrics of the University Hospital of Zurich. The end of birth (crowning of the head and fetal extraction) with the manual actions and manoeuvers performed was recorded on video in 100 births. Procedures were analysed afterwards by a senior consultant and evaluated with the staff involved. RESULTS We found frequent notable omissions during vaginal deliveries, concerning technical and nontechnical skills. Those aspects included inappropriate aseptic technique (e.g., no sterile underlay or sterile gloves), improper fetal head slowdown during expulsion, lack of visualisation of the perineum during fetal extraction/expulsion, lack of hip, shoulder and arm guiding while extracting the fetus, inappropriate episiotomy technique (wrong handling of the scissors, cutting angle too steep) and improper communication between the woman giving birth and the staff. During vacuum extractions, incorrect positioning of the cup, and inappropriate direction of pulling and handling of the cup were recorded. CONCLUSIONS Video analysis of obstetric procedures in the labour ward is an easily applicable and very useful tool for teaching and learning purposes. It contributes to showing and improving the quality of procedures and the interactions of the staff and can be used for staff evaluation. ​ Registered at ClinicalTrials.gov (registration number NCT02295904)